2012
DOI: 10.7196/samj.6059
|View full text |Cite
|
Sign up to set email alerts
|

Reasons why patients with primary health care problems access a secondary hospital emergency centre

Abstract: Emergency centres (ECs) provide emergency care to people with acute trauma and illness who require the services and expertise available at a hospital.1 However, the presenting complaints at an EC overlap considerably with those encountered at primary healthcare (PHC) level.2 Studies suggest that one-third to two-thirds of patients attend ECs with problems that could have been managed at a PHC level. 2-5The South African Triage Score (SATS) (previously known as the Cape Triage Score) 6-7 is routinely used at Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 9 publications
5
45
0
Order By: Relevance
“…Only 13 of the 23 cross‐sectional studies reported a sample size justification or power description or provided variance and effect estimates. It was not possible to calculate the response rate for one study, due to insufficient detail given 18. However, for the 22 studies that did provide this information, the mean response rate was 77% and the range was 45% to 99%.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only 13 of the 23 cross‐sectional studies reported a sample size justification or power description or provided variance and effect estimates. It was not possible to calculate the response rate for one study, due to insufficient detail given 18. However, for the 22 studies that did provide this information, the mean response rate was 77% and the range was 45% to 99%.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies did not provide sufficient information about ethical or research approvals and two studies lacked information about the considerations of the relationship between the research and the patient. Some studies used multiple methods incorporating a range of qualitative methods across whole populations, while others employed simpler designs with less comprehensive samples, for example, multisite studies using focus groups and interviews39 and multisite surveys24 compared to single‐site qualitative studies 18…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations